Acacetin Protects Mice from Staphylococcus aureus Bloodstream Infection by Inhibiting the Activity of Sortase A - Bi, Chongwei; Dong, Xiaoyun; Zhong, Xiaobo; Cai, Hongjun; Wang, Dacheng; Wang, Lin (Molecules (Basel, Switzerland), 2016)
Staphylococcus aureus (S. aureus) is a major cause of infection in hospitals and communities. Widespread dissemination of multi-drug resistant S. aureus is a serious threat to the health of humans and animals. An anti-virulence strategy has been widely considered as an alternative therapeutic approach. Inhibitors of virulence factors are able to treat S. aureus infections without influencing the growth or viability of bacteria and rarely lead to bacterial resistance. Sortase A (SrtA) is a membrane-associated cysteine transpeptidase that catalyzes up to 25 surface proteins that covalently bind to cell wall peptidoglycans. In S. aureus, most of these surface proteins have been identified as important virulence factors that are vital in bacterial pathogenesis. In the present study, we show that acacetin, a natural flavonoid compound, inhibits the activity of SrtA in S. aureus (IC50 = 36.46 ± 4.69 μg/mL, 128 μM) which affects the assembly of protein A (SpA) to cell walls and reduces the binding of S. aureus to fibrinogen (Fg). The mechanism of the interaction between acacetin and SrtA were preliminarily discussed using molecular dynamics simulations. The results suggested that acacetin adopted a compact conformation binding at the pocket of the SrtA via residues Arg-139 and Lys-140. By performing an animal infection model, we demonstrated that acacetin was able to protect mice from renal abscess formation induced by S. aureus and significantly increased survival rates. Taken together, these findings suggest that acacetin may be a promising candidate for the development of anti-S. aureus drugs.